Experimental Therapy of Cladosporiosis and Sporotrichosis with 5-Fluorocytosine - Block, Edward R. (1973)
Cladosporium trichoides and Sporothrix schenckii are fungi known to be pathogenic for man. No effective chemotherapy is available for cladosporiosis, and systemic sporotrichosis can be very resistant to antifungal chemotherapy. Experimental infections of mice with these fungi resembled their respective infections in man and provided a model for evaluating a new antifungal agent, 5-fluorocytosine (5-FC). Our results with four isolates of C. trichoides demonstrated a statistically significant dose-related therapeutic effect with 5-FC. Mortality was significantly reduced in all treatment groups, and survivors showed no clinical sign of disease despite positive brain cultures. Results with a single isolate of S. schenckii were less encouraging. Fatality rate was significantly decreased in all treatment groups, but no trend was noted with increasing 5-FC dosage. Survivors manifested the signs of active disease, and all liver and spleen cultures were positive for S. schenckii. These results indicated that (i) 5-FC may be the first drug useful in the treatment of cladosporiosis, and (ii) 5-FC may have only limited therapeutic benefit in systemic sporotrichosis.